Insight Into Interactions of Thermoacidophilic Archaea With Elemental Sulfur: Biofilm Dynamics and EPS Analysis - Zhang, Ruiyong; Neu, Thomas R.; Li, Qian; Blanchard, Véronique; Zhang, Yutong; Schippers, Axel; Sand, Wolfgang (Frontiers in Microbiology, 2019)
Biooxidation of reduced inorganic sulfur compounds (RISCs) by thermoacidophiles is of particular interest for the biomining industry and for environmental issues, e.g. formation of acid mine drainage (AMD). Up to now, interfacial interactions of acidophiles with elemental sulfur as well as the mechanism of sulfur oxidation by acidophiles, especially thermoacidophiles, are not yet fully clear. This work focused on how a crenarchaeal isolate Acidianus sp. DSM 29099 interacts with elemental sulfur. Analysis by Confocal laser scanning microscopy (CLSM) and Atomic force microscopy (AFM) in combination with Epifluorescence microscopy (EFM) shows that biofilms on elemental sulfur are characterized by single colonies and a monolayer in first stage and later on 3-D structures with a diameter of up to 100 micrometers. The analysis of extracellular polymeric substrances (EPS) by non-destructive lectin approach (fluorescence lectin-barcoding and analysis) using several fluorochromes shows that intial attachment was featured by footprints rich in biofilm cells were embeded in a EPS matrix consists various of glycoconjugates. Wet chemistry data indicate that carbohydrates, proteins, lipids and uronic acids are the main components. Attenuated reflectance (ATR)-Fourier transformation infrared spectroscopy (FTIR) and high-performance anion exchange chromatography with pulsed amperometric detection (HPAE-PAD) indicate glucose and mannose as the main monosaccharides in EPS polysaccharides. EPS composition as well as sugar types in EPS varies according to substrate (sulfur or tetrathionate) and lifestyle (biofilms and planktonic cells). This study provides information of the building blocks/make up as well as dynamics of the thermoacidophilic archaeon biofilms in extremely acidic environments.